PENGUATAN PENDIDIKAN KARAKTER (PPK) BERBASIS BUDAYA SEKOLAH - Niswatul Mufarrochah; Mohammad Makinuddin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2021)
Abstract: This study aims to describe the imple-mentation of the strengthening of character education based on school culture in SMP Khadijah 2 Surabaya along with inhibiting factors and school strategies in overcoming inhibiting factors Strengthening school culture-based character education at SMP Khadijah 2 Surabaya. This research is a qualitative descriptive study, data collection techniques used are observation, interview and documentation. Data analysis uses interactive miles, hubermen and saldana data analysis models, namely data condensation, data presentation and conclusion drawing. The results showed that the strengthening of school culture-based character edu-cation was done by accustoming the main values of religious values, providing role models among school members, involving all stakeholders, developing and complying with school norms, regulations and traditions, developing Branding Schools, developing literacy activities, developing interests, talents, and potentials through extracurricular activities and providing mentoring. The impact of the application of Strengthening character education at SMP Khadijah 2 Surabaya is that there is a significant increase in the character development of students, students are accustomed to doing 5S, students who usually pray not on time become prayers on time, students who are usually late for school, now are not late to enter school.Keywords: character education, school, values